2022
DOI: 10.1186/s13073-022-01056-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined exome and transcriptome sequencing of non-muscle-invasive bladder cancer: associations between genomic changes, expression subtypes, and clinical outcomes

Abstract: Background Three-quarters of bladder cancer patients present with early-stage disease (non-muscle-invasive bladder cancer, NMIBC, UICC TNM stages Ta, T1 and Tis); however, most next-generation sequencing studies to date have concentrated on later-stage disease (muscle-invasive BC, stages T2+). We used exome and transcriptome sequencing to comprehensively characterise NMIBCs of all grades and stages to identify prognostic genes and pathways that could facilitate treatment decisions. Tumour gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…As histopathological tissues were stained with H&E, it was demonstrated that there were no considerable differences between Groups 2 and 3. With a close tie to cigarette smoking, inflammatory channels of spread are essential preconditions of BC development, with elevated PAF release potentially contributing to cancer cell development, spread, and tumor tissue production, confirmed and described by several past studies [11,12,24,32,36,[38][39][40].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…As histopathological tissues were stained with H&E, it was demonstrated that there were no considerable differences between Groups 2 and 3. With a close tie to cigarette smoking, inflammatory channels of spread are essential preconditions of BC development, with elevated PAF release potentially contributing to cancer cell development, spread, and tumor tissue production, confirmed and described by several past studies [11,12,24,32,36,[38][39][40].…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, cancer-associated genes (comprising oncogenes and tumor suppressor genes) are mutated, causing cells to grow rapidly, thus leading to cancer. Among many cancer-associated genes, nine BCassociated genes were selected as the most common in this study [24,35,36,38], relying on NGS technology, which identified thirteen observable mutations in 7 of 9 cancer-associated genes of DNA samples among non-smoking and smoking participants with BC. These mutations were confirmed by structural signature variation (SSV), detecting a similar number of mutation patterns in the studied genes.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies focused on bladder cancer, and NMIBC-related research is more limited. Goel et al used exome and transcriptome sequencing to characterise all grades of NMIBCs to determine prognostic genes and indicated that multi-omic data may help to better identify treatment in high-risk patients [11].…”
Section: Introductionmentioning
confidence: 99%